Pengaruh Investasi dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Suherman; Rika Neldawaty; abd halim (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to examine the role of Investment in economic development, which must be considered by various government and private parties when allocating capital or regional spending. In this study, we use investment and labor data on economic growth in Jambi Province from 2014 to 2023. The results of this study indicate that, in the t-test, the significance value of Investment partially influences economic growth. While labor shows partial influence, it does not have a significant influence on economic growth, as indicated by the hypothesis test, with a p-value of 0.040. The results of the test show that the simultaneous investment variables (X1) and labor (X2) have a significant effect on the economic growth variable (Y). Investment (X1) and labor (X2) account for 96% of the effect on economic growth (Y).